2013
DOI: 10.1182/blood-2013-02-487074
|View full text |Cite
|
Sign up to set email alerts
|

CMV reactivation after allogeneic HCT and relapse risk: evidence for early protection in acute myeloid leukemia

Abstract: Key Points CMV reactivation after HCT is associated with a reduced risk of early relapse in patients with AML but not other disease groups. The benefit, however, is offset by an increased risk of nonrelapse mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
240
9
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(280 citation statements)
references
References 27 publications
26
240
9
5
Order By: Relevance
“…Previous 34 as well as recently published data show that CMV reactivation confers a protective effect against early (100-day) 35 or even later relapses 36 in patients who received an allo-HCT for AML. Even though we did not include incidence and time of CMV reactivation as a variable in our analysis, we observed a favorable effect of recipient CMV seropositivity at the time of transplantation, resulting in a lower CIR.…”
Section: Discussionmentioning
confidence: 87%
“…Previous 34 as well as recently published data show that CMV reactivation confers a protective effect against early (100-day) 35 or even later relapses 36 in patients who received an allo-HCT for AML. Even though we did not include incidence and time of CMV reactivation as a variable in our analysis, we observed a favorable effect of recipient CMV seropositivity at the time of transplantation, resulting in a lower CIR.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3] This was demonstrated in acute myeloid leukemia (AML) and chronic myeloid leukemia (CML). 4 Other studies have demonstrated both early and late protective effects, but all have been on matched related or unrelated donors.…”
mentioning
confidence: 99%
“…In addition to the absence of a predictable link between KIR genotype and phenotype, one must also consider potential viral imprinting of both the donor and recipient NK cell repertoires. Given that adaptive NK cell responses to CMV can be transferred from an allogeneic donor to the recipient (21), it was speculated that high frequencies of educated and differentiated NK cells in the donor or the emergence of such NK cell populations in the recipient may contribute to the reduced risk for relapse associated with CMV reactivation in myeloid malignancies (22)(23)(24). This hypothesis was recently supported by the observed link among CMV reactivation, expansion of CD56 dim CD57 + NKG2C + NK cells, and reduced leukemia relapse in patients receiving reduced-intensity conditioning (RIC) (25).…”
mentioning
confidence: 99%